PANDANGAN TENTANG HUKUM DAN KEADILAN - Jarot Jati Bagus Suseno (Ilmu Hukum Prima (IHP), 2018)
Law as a method is always declared to be generally applicable to anyone and anywhere in the territory of the country, without discrimination. Although there are exceptions stated explicitly and based on certain reasons that can be accepted and justified. Basically, the law does not apply in a discriminatory manner, except for law enforcement officials or organizations in social reality that have imposed the law in a discriminatory manner. Finally, law enforcement does not reflect the existence of legal certainty and a sense of justice in society. Law will be meaningful if human behavior is influenced by law and if people use the law according to their behavior, while on the other hand the effectiveness of the law is closely related to the problem of legal compliance as the norm. This is different from the basic policies that are relatively neutral and depend on the universal value of the objectives and reasons for establishing legislation. In practice we see that there are laws which are mostly obeyed and there are laws that are not obeyed. The legal system will clearly collapse if everyone does not comply with the law and the law will lose its meaning. The ineffectiveness of laws tends to influence the timing of attitudes and quantity of non-compliance and has a real effect on legal behavior, including behavior of lawbreakers. This condition will affect law enforcement which guarantees certainty and justice in the community.